2019
DOI: 10.1016/j.ijso.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based perioperative management of patients with high serum potassium level in resource-limited areas: A systematic review

Abstract: This systematic review was conducted according to the Preferred Reporting Items for Systematic review and meta-analysis (PRISMA) protocol. Search engines like PubMed through HINARI, Cochrane database, GoogleScholar and ScienceDirect were used to find high-level evidence that helps to draw appropriate conclusions. Potassium is a critical electrolyte for cellular functions and its serum concentration must be precisely maintained between 3.5 and 5.5 mEq/L. A multidisciplinary approach is crucial to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Some suggest postponing surgery in patients with preoperative potassium concentration >6 mmol/L. 10 In our patient's case, the preoperative potassium concentration was only determined to be >6 mmol/L the day before surgery. Other results on the day of surgery indicated…”
Section: Discussionmentioning
confidence: 57%
“…Some suggest postponing surgery in patients with preoperative potassium concentration >6 mmol/L. 10 In our patient's case, the preoperative potassium concentration was only determined to be >6 mmol/L the day before surgery. Other results on the day of surgery indicated…”
Section: Discussionmentioning
confidence: 57%
“…Beta-adrenergic receptor blockers (e.g., metoprolol), potassium-sparing diuretics (e.g., spironolactone), metabolic acidosis, ischemic necrosis, hemolysis, rhabdomyolysis, and severe hyperglycemia have all been found to increase serum potassium as well. While it is not always possible to avoid these medications and situations, it is essential to do whenever clinically feasible to lower the likelihood of inducing significant hyperkalemia in susceptible patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in serum sodium and serum potassium may be associated with medical and surgical disorders, drug intake and have a potential to affect the anaesthetic management and the outcomes. [ 34 35 36 37 ] One study involving intermediate surgeries (n = 20915),[ 20 ] and two studies involving minor and intermediate surgeries (n = 765) did not report any adverse outcomes related to deranged serum electrolytes. [ 21 23 ] Three studies involving all three categories of surgeries (n = 608), showed influence on outcomes in five patients with deranged serum sodium.…”
Section: Guidelines and Recommendationsmentioning
confidence: 99%